Work, family and social environment in patients with Fibromyalgia in Spain: an epidemiological study: EPIFFAC study - Collado, Antonio (BMC Health Serv Res, 2014)
BACKGROUND: Fibromyalgia (FM) is a condition characterized by widespread pain, estimated to affect 2.4% of the Spanish population. Nowadays, there are no consistent epidemiological studies on the actual impact of the disease on work and family of these patients in a representative manner; therefore, the purpose of the study is to analyze the impact on family, employment and social environment in a representative sample of patients with FM attending Primary Public Care Centers in Spain. METHODS: We carried out an epidemiological study, with a probability sampling procedure, stratified, relative to the municipality size and the number of health centres, seeking territorial representation. The survey was conducted using a self-administered structured questionnaire. RESULTS: A sample of 325 patients with FM was studied in 35 Primary Health Care Centers (PHCCs). The sample is composed of 96.6% of women, 51.9 (8) years of mean (standard deviation- sd) age. Ninety-three percent of the patients have worked throughout their life. Mean (sd) age onset of symptoms was 37 (11) years and diagnosis of FM was established 6.6 (8) years later. Family Environment: Fifty-nine percent of patients have difficulties with their partner. Forty-four percent of the patients report to be fairly or totally dependent on a family member in household chores. The household income decreased a mean (sd) of 708 (504) Euros/month in 65% of the patients. In 81% of the patients, there was an increase in extra expenses related to the disease with a mean (sd) of 230 (192) Euros/month. Working environment: At the moment of the study, 45% of the patients had work activity (34% were working and 11% were at sick leave), 13% were unemployed seeking job and 42% were not in the labor force. Twenty-three percent of patients had some degree of permanent work disability pension. Social Environment: The degree of satisfaction with health care professionals was low and twenty-six percent of the patients were members of specific patients associations. CONCLUSIONS: This study finds that people with FM who visit PHCCs of Spain experience a high impact on families and employment with heavy loss of ability to work.